Kepastian Hukum Bagi Investor Fintech P2P Lending Dalam Kepailitan Bisnis Menggunakan Pendekatan Business Ready - Yohanes B. Cahayamisjuan (SAPIENTIA ET VIRTUS, 2024)
This writing discusses the influence of legal certainty in the Bankruptcy and Delayed Debt Payment Obligation (PKPU) Law on investor interest in the Fintech Peer-to-Peer (P2P) Lending sector, using the legal certainty theory by Lon Fuller. A potential solution in the form of the B-Ready approach is also proposed to enhance legal certainty for investors through the revision of the Bankruptcy and PKPU Laws. This approach is normatively analyzed through statutory and conceptual approaches. Research findings indicate that the current Bankruptcy and PKPU Laws do not fulfill Fuller's eight elements of legal certainty, particularly regarding the prohibition of conflicting regulations and the alignment of rules with their practical application. This could potentially detrimentally affect investor interest in the Fintech P2P Lending sector due to legal uncertainty jeopardizing their investments. The B-Ready approach emerges as a potential solution by identifying seven aspects in the Draft Bankruptcy and PKPU Laws that can facilitate business ease for investors when facing business bankruptcy. Overall, a review of the Bankruptcy and PKPU Laws is crucial to establish a clearer and advantageous legal environment for investors in the Fintech P2P Lending sector. The B-Ready approach holds potential as a foundation for revising regulations, ensuring the necessary legal certainty for investors.